2019
DOI: 10.1021/acs.langmuir.9b01288
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and Protein Transfer between Nanolipoprotein Particles and Supported Lipid Bilayers

Abstract: A nanolipoprotein particle (NLP) is a lipid bilayer disc stabilized by two amphipathic "scaffold" apolipoproteins. It has been most notably utilized as a tool for solubilizing a variety of membrane proteins while preserving structural and functional properties. Transfer of functional proteins from NLPs into model membrane systems such as supported lipid bilayers (SLBs) would enable new opportunities for example: two-dimensional protein crystallization and studies on protein-protein interactions. This work used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…With CHO cells, most of the transferred MPs are localized in the cytoplasm. It has been shown that the composition of supported lipid bilayers affects the transfer of MPs from NDs (Dang et al, 2019). Different membrane compositions of the analyzed cell lines might therefore contribute to the observed preference in MP localization.…”
Section: Figure 12mentioning
confidence: 98%
See 2 more Smart Citations
“…With CHO cells, most of the transferred MPs are localized in the cytoplasm. It has been shown that the composition of supported lipid bilayers affects the transfer of MPs from NDs (Dang et al, 2019). Different membrane compositions of the analyzed cell lines might therefore contribute to the observed preference in MP localization.…”
Section: Figure 12mentioning
confidence: 98%
“…According to the fusion pore model for the transfer of cargo from NDs to bicelles, the NDs are suggested to align in a planar orientation on top of the target bilayer (Lai et al, 2015). The MPs may then spontaneously transfer between nanoparticle and cell membranes (Dang et al, 2019). Two contact sites of the MP/ND particles with the cell membrane are possible.…”
Section: Figure 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, NLP-mediated protein delivery is believed to be a spontaneous exchange of proteins between NLPs and plasma membrane, thus minimizing the potential off-target effects of the delivery system. 18 Given the facile synthesis of NLPs and the simplicity of this protein transfection system, we sought to determine if this system could be used to rapidly engineer new oncoproteindriven cancers. Half of all drugs that have been approved to treat cancer in the past decade target cell surface receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to existing protein delivery systems that risk denaturing the proteins they carry, either by harsh packaging or endosomal lytic processes, NLPs maintain correct folding of mammalian cell surface receptors. ,, NLPs, in contrast to other protein delivery systems, do not require cell membrane disruption , and diffuse readily due to their small size relative to silica or poly­(lactic- co -glycolic acid) (PLGA) nanoparticles, ,, potentially resulting in a more efficient transfer of proteins into cells. Furthermore, NLP-mediated protein delivery is believed to be a spontaneous exchange of proteins between NLPs and plasma membrane, thus minimizing the potential off-target effects of the delivery system …”
Section: Introductionmentioning
confidence: 99%